The impact of cardiomotor rehabilitation on endothelial function in elderly patients with chronic heart failure - Juming Chen (BMC, 2021)
Abstract Background To explore the effects of cardiac exercise rehabilitation on peripheral blood endothelial progenitor cells (EPC) in elderly patients with chronic heart failure. Methods 80 elderly patients with chronic heart failure were selected from March 2017 to March 2019 and randomly divided into two groups (N = 40). The control group was treated routinely and walked freely for 30–60 min every day. The patients in the exercise rehabilitation group developed a cardiac exercise rehabilitation plan. Then, cardiac function and peripheral blood B-natriuretic peptide (BNP) levels in the two groups were compared. The cell viability, proliferation, apoptosis, and invasion ability of EPCs were detected. The levels of the PI3K/AKT pathway and eNOS and VEGF were compared. Results There were no significant differences in all indexes between the two groups before treatment (P > 0.05), and both improved significantly after treatment (P < 0.05). After treatment, LVEF and LVFS in the exercise rehabilitation group were significantly higher than those in the control group (P < 0.05), and LVEDD and LVESD were significantly lower than those in the control group (P < 0.05). The BNP level in the exercise rehabilitation group was significantly lower than that in the control group (P < 0.05). The cell viability, proliferation, invasion ability of EPC, and the levels of PI3K, AKT, eNOS, and VEGF mRNA and protein in the exercise rehabilitation group were significantly higher than those in the control group. Apoptosis rate was significantly lower than those in the control group (P < 0.05). Conclusions Visceral exercise rehabilitation can improve cardiac ejection and myocardial function in elderly patients with chronic heart failure, and can promote the vitality, proliferation, and invasion of peripheral blood EPC, and promote the expression of eNOS and VEGF by upregulating the PI3K/AKT pathway to promote angiogenesis and endothelial function.